Development of Textured ITO Optical Windows for Photovoltaic Applications. (26th May 2013) - Tamilselvan, N.; Thilakan, Periyasamy
Abstract : ITO thin films were deposited on glass substrates using rf magnetron sputtering. Deposition parameters such as the rf power and the oxygen dilution to the plasma are investigated. Films deposited with an increase in rf power were resulting in the film preferential orientation along (100) plane. Oxygen dilution to the plasma at low rf power of 30 W was found to result in a change in preferential orientation from (100) plane to (111) plane. SEM analysis revealed a spotty surface morphology for the (100) films and a granular morphology for the (111) films. The highest transmittance was found for the oxygen diluted (111) film. The highest optical bandgap of 4.33 eV was observed for the pure Ar deposited film. Details are discussed.